Motivation and learning media: How do they affect mathematics learning outcomes after the covid-19 pandemic? - Pramita, Mitra; Sukmawati, R Ati; Wiranda, Nuruddin (Al-Jabar: Jurnal Pendidikan Matematika, 2022)
After the pandemic, people began to adjust to the changes during the pandemic. The rapid progress and development of information and technology are now entering the world of education. Information technology has begun to be widely used to support the smooth running of the teaching and learning process, one of which is to support student learning outcomes. This study aimed to determine the differences in student learning outcomes in the control and experimental classes by considering students' learning motivation. This type of research is an experimental study with a 2×2 factorial design. Discrete mathematics learning outcomes for even-semester students in 2021/2022 will be grouped based on learning media (PowerPoint and Kahoot) and student motivation (high and low). To find out the differences in student learning outcomes, a 2-way ANOVA test was carried out using SPSS. The results of this study show significant differences in student learning outcomes between students with high learning motivation and those with low learning motivation. There is no significant difference in learning outcomes between Kahoot learning media and PowerPoint learning media. Then it is known that other factors affect student concentration; namely, an interaction between learning media and learning motivation influences students' learning outcomes. The Kahoot media was proven to make the learning atmosphere more fun during the learning activities. Students were more active in participating in the learning process.